2022
DOI: 10.3390/vaccines11010061
|View full text |Cite
|
Sign up to set email alerts
|

An Immunoinformatics Approach to Design a Potent Multi-Epitope Vaccine against Asia-1 Genotype of Crimean–Congo Haemorrhagic Fever Virus Using the Structural Glycoproteins as a Target

Abstract: Crimean–Congo haemorrhagic fever (CCHF), caused by Crimean–Congo haemorrhagic fever virus (CCHFV), is a disease of worldwide importance (endemic yet not limited to Asia, Middle East, and Africa) and has triggered several outbreaks amounting to a case fatality rate of 10–40% as per the World Health Organization. Genetic diversity and phylogenetic data revealed that the Asia-1 genotype of CCHFV remained dominant in Pakistan, where 688 confirmed cases were reported between the 2012–2022 period. Currently, no appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…A more robust immunological response is produced as a result of the linker's positive charge stabilizing the contact between the antigen and carrier protein. 85 Furthermore, EAAAK, an empirical-helical linker, was employed to increase the stiffness, boost the stability of the fusion protein, and improve the bifunctional catalytic activity. 83 An HBHA conserved adjuvant, which has been recognized as an effective and beneficial adjuvant, was also added to the vaccine sequence to boost the immunogenicity of the designed vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more robust immunological response is produced as a result of the linker's positive charge stabilizing the contact between the antigen and carrier protein. 85 Furthermore, EAAAK, an empirical-helical linker, was employed to increase the stiffness, boost the stability of the fusion protein, and improve the bifunctional catalytic activity. 83 An HBHA conserved adjuvant, which has been recognized as an effective and beneficial adjuvant, was also added to the vaccine sequence to boost the immunogenicity of the designed vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…A protein antigen is frequently joined to a carrier protein, such as a bacterial toxin, by using the KK linker. A more robust immunological response is produced as a result of the linker’s positive charge stabilizing the contact between the antigen and carrier protein . Furthermore, EAAAK, an empirical-helical linker, was employed to increase the stiffness, boost the stability of the fusion protein, and improve the bifunctional catalytic activity .…”
Section: Discussionmentioning
confidence: 99%
“…The KK linker is widely used to attach a protein antigen to a carrier protein, like a bacterial toxin. The positive charge of the linker stabilizes the interaction between the carrier protein and antigen, resulting in a stronger immune response ( 77 ). Furthermore, the fusion protein’s stiffness, stability, and bi-functional catalytic activity were all improved by the use of an empirical-helical linker, EAAAK ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent proteomics-based trends in vaccine development revolve around identifying immunogenic surface-exposed antigens, which can activate an immune response [ 39 ]. An immunoinformatics approach assisted by proteome screening has been successfully used to design multi-epitope chimeric vaccines against Hendra henipavirus and Crimean-Congo hemorrhagic fever virus [ 40 , 41 ]. In another study, the proteome screening of human papillomavirus (HPV) via computational tools identified highly conserved epitopes from the N-terminus of HPV-58 L2 capsid protein.…”
Section: Chimeric Vaccines: Future Of Vaccinology With State-of-the-a...mentioning
confidence: 99%